Autoren in religiösen literarischen Texten der späthellenistischen und der frühkaiserzeitlichen Welt Zwölf Fallstudien - Becker, Eve-Marie; Ruepke, Joerg (Mohr Siebeck, 2018)
The contributors to this volume discuss the formation and transformation of ancient concepts of authorship, specifically among those types of texts that are classified as "religious literature" - whether Greco-Roman, early Jewish, and early Christian. In twelve case studies spanning the time from Ben Sira to Tertullian, various ways of how authors considered themselves to be individual producers of texts and religious voices are carved out. The volume presents authors who fashion themselves either as orthonymous, anonymous, or pseudepigraphic writers, and who share the idea of being "religious agents". The search for these religious voices undertaken here is a valuable contribution to both research in ancient "Autorforschung" and the religio-historical study of how religious knowledge was produced in the ancient Mediterranean world.